Improvement of power quality of CFL bulbs using active power factor correction circuit - Modak, Sudipta; Das, Tapas Kumar; Nabi, Mohammad Rafiqun (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.